Does financial inclusion reduce poverty and income inequality in developing countries? A panel data analysis - Md Abdullah Omar; Kazuo Inaba (Journal of Economic Structures, 2020)
Financial inclusion is a key element of social inclusion, particularly useful in combat-ing poverty and income inequality by opening blocked advancement opportunities for disadvantaged segments of the population. This study intends to investigate the impact of financial inclusion on reducing poverty and income inequality, and the determinants and conditional effects thereof in 116 developing countries. The analysis is carried out using an unbalanced annual panel data for the period of 2004-2016. For this purpose, we construct a novel index of financial inclusion using a broad set of financial sector outreach indicators, finding that per capita income, ratio of internet users, age dependency ratio, inflation, and income inequality significantly influence the level of financial inclusion in developing countries. Furthermore, the results provide robust evidence that financial inclusion significantly reduces poverty rates and income inequality in developing countries. The findings are in favor of further promoting access to and usage of formal financial services by marginalized segments of the popu-lation in order to maximize society's overall welfare.
Keywords: G21; I32; O11; O15; O16; O53; O54; O55; 330; Financial inclusion; Poverty; Income inequality; Developing countries